AN APPLICATION FOR DETERMINING SUPPLY CHAIN INTEGRATION PROBLEMS VIA A MCDA METHODOLOGY: A CASE STUDY OF MANUFACTURING FIRMS IN ORDU PROVINCE - AYTEKİN, Ahmet; Korucuk, Selçuk (Journal of process management and new technologies, 2023)
Businesses are changing their organizational structures in order to compete and increase consumer value. They try to enhance their flexibility in order to respond to changing market needs and meet incoming demand. For this purpose, supply chain integration is becoming increasingly important in businesses and plays a crucial role in improving corporate sustainability. Integration's purpose is to enable the effective and efficient flow of products/services, information, money, and decisions, as well as to give the most value to the customer at the lowest feasible cost. However, business supply chain integration encounters many obstacles. The integration of the supply chain is considered an important key element for the sustainability of production, for the planning and efficiency of processes as well as for the quality and efficiency of services. It is clear that the development of supply chain integration, especially according to business requirements and needs, will also bring sustainable success in the long term. Based on the issues identified as barriers to supply chain integration, it can offer various suggestions at the desired level sufficient to resolve the issue(s) on the ground. In this context, the study investigated and determined the obstacles to supply chain integration in manufacturing businesses, with the goal of weighting the determined criteria. For this purpose, the Interval Valued Fermatean Fuzzy SWARA method was employed to weight the identified criteria. As a result of the analyses, it was concluded that Lack of Information Technology and Sharing " is the most important criterion among the obstacles to supply chain integration, and " Incompatibility of Operational and Strategic Goals " is the least important criterion.